Artikel Pengaruh Lingkungan Kerja, Kepemimpinan, Rekan Kerja, Keamanan Pekerjaan, dan Gaji terhadap Kinerja Karyawan yang Dimediasi oleh Kepuasan Kerja di Perusahaan Manufaktur di Kota Batam. - Yuswardi, Yuswardi; Mon, Muhammad Donal; Ginting, Rezky Dwiham (Universitas Islam Kadiri, 2024)
The performance of workers, particularly in the manufacturing sector, has become a significant concern, encompassing issues related to unskilled human resources, educational levels, economic systems, and inadequate working environments. This research is centered on manufacturing companies in Batam City, examining the interconnectedness of work environment, leadership, colleagues, job security, and salary in influencing employee performance, with job satisfaction acting as a mediator. Primary data for the study is collected through online distributed questionnaires, employing a purposive sampling method for respondent selection. A negative work environment has a detrimental impact on employee performance, fostering dissatisfaction and diminishing overall output. Ineffectual leadership contributes to employee dissatisfaction and subsequently hampers performance. Collaborative support from colleagues plays a pivotal role in enhancing employee performance. A secure work environment positively correlates with improved employee performance. Adequate and timely salary payments commensurate with job responsibilities contribute to enhanced employee performance. Employee satisfaction emerges as a key factor influencing performance, with higher satisfaction levels corresponding to increased productivity.